AuBr3-catalyzed azidation of per-O-acetylated and per-O-benzoylated sugars - Rajput, Jayashree; Hotha, Srinivas; Vangala, Madhuri (Beilstein Journal of Organic Chemistry, 2018)
Herein we report, for the first time, the successful anomeric azidation of per-O-acetylated and per-O-benzoylated sugars by catalytic amounts of oxophilic AuBr3 in good to excellent yields. The method is applicable to a wide range of easily accessible per-O-acetylated and per-O-benzoylated sugars. While reaction with per-O-acetylated and per-O-benzoylated monosaccharides was complete within 1–3 h at room temperature, the per-O-benzoylated disaccharides needed 2–3 h of heating at 55 °C.
Keywords: acylated sugars; azidation; gold(III) bromide; N-glycoside; oxophilicity